The Impact of Virtual Reality, Augmented Reality, and Interactive Whiteboards on the Attention Management in Secondary School STEM Teaching - Erofeeva, Maria; Klowait, Nils Oliver (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Today, technologies like interactive whiteboards, augmented and virtual reality serve as instructional aids to facilitate interactive learning. The aim of this paper is to study how the use of such technologies impacts the dynamics of classroom attention management. Employing a multimodal conversation-analytic framework, we analyze video recordings of the first encounters with interactive whiteboards, augmented reality and virtual reality across twelve in-person classroom lessons set in four Russian secondary schools. This paper highlights how the teacher, faced with a breakdown of regular channels for managing attention (such as mutually-orientable gaze), uses their voice and body to facilitate the temporal coordination of student contributions, maintain focus on a given classroom activity, and visibly monitor classroom dynamics. The findings suggest means to alleviate tensions between new and old teaching methods, and provide further evidence on the need for a granular vocabulary for the analysis of body-orientation in a classroom context.